What Role for Diaspora Expertise in Post-Conflict Reconstruction? Lessons from Afghanistan, and West Bank and Gaza - World Bank (World Bank, Washington, DC, 2012)
The Afghanistan Expatriate Program (AEP) and the Palestinian Expatriate Professional Project (PEPP) recruit expatriates through a merit-based system to build capacity in government departments and agencies in Afghanistan and West Bank and Gaza respectively. Beyond individual success stories, both initiatives faced the tremendous challenge of translating individual inputs into institutional capacity building and as a result, both programs could not generate the expected increase in capacity of the local civil service. Indeed, strengthening management and technical capabilities of the ministries and agencies in both projects was achieved only sporadically. The one real value of the expatriate programs was the expatriates' knowledge of the local language and environment and, in the case of the AEP, a single window funding for short-term consultants. However, such programs are only stop-gap and unless they build capacity over the medium term, as donor funding diminishes they are unsustainable for recipient governments. This dissemination note aims to capture lessons learned from the AEP and PEPP programs.